Beliefs about the causes of obesity in a national sample of 4th year medical students. Issue 11 (November 2015) - Phelan, Sean M.; Burgess, Diana J.; Burke, Sara E.; Przedworski, Julia M.; Dovidio, John F.; Hardeman, Rachel; Morris, Megan; van Ryn, Michelle
Highlights Fourth year medical students demonstrate knowledge about the complex causes of obesity. Overeating, physical inactivity, and nutritional knowledge are rated as most important. Social and physiological causes were rated as less important. Four distinct patterns of beliefs were identified, which may have clinical implications.